Limited immediate effect of artificial light of realistic intensity on flight behaviour of commuting pond bat (Myotis dasycneme) - Claire Hermans; Laura Kijm; Marieke Paardekooper; Jens C. Koblitz; Peter Stilz; Anne-Jifke Haarsma; Marcel E. Visser; Kamiel Spoelstra (Basic and Applied Ecology)
Artificial light at night can act as a barrier and cause habitat fragmentation, especially for bat species that are generally considered to be light-averse. Bats use linear structures to commute from their roost to their foraging areas. Trawling bats such as the pond bat (Myotis dasycneme) forage predominantly above water bodies and use waterways as commuting routes. Artificial light along these potentially leads to interruptions of commuting routes, or changes in flight behaviour of trawling bats, but impact of light may vary with light spectrum and intensity. Here, we tested whether pond bats change their flight speed and straightness in response to four light spectra at two light intensities by placing an experimental lamp post at bridges over waterways that are used by pond bats as commuting routes. We used a microphone array to precisely reconstruct the flight path of each passing bat and calculate flight parameters. Flight speed of commuting pond bats was unaffected by the presence of light, regardless of the light spectrum. Pond bats only fly straighter when exposed to white light (3000 K). The short presence of a lamp post with realistic light intensity on a bridge may therefore not act as a barrier. However, other direct effects cannot be excluded and the long-term presence of a similar light installation may still have impact.